MOTIVASI PESERTA DIDIK DALAM BELAJAR BOLA VOLI DI SEKOLAH MENENGAH ATAS NEGERI 9 PONTIANAK - Billy Ervandy; Andika Triansyah; Fitriana Puspa Hidasari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis research discussed about lack of motivation of students in participating in learning activities that cause most students do not really take part in learning, both in listening to the teacher's explanation and when carrying out the practice of volleyball. This study aimed to determine how much motivation students learn volleyball in class XI at Pontianak State High School 9. This research is a descriptive research. The method used is a survey with data collection techniques using questionnaires. The population in this study were all students of Pontianak 9 High School, the sampling technique used was purposive sampling. The sample used was students of class XI IPS totaling 93. The results showed that the motivation of students in learning volleyball at Pontianak State High School was in the category of "not very good" by 0% (0 students), "not good" by 1.08% (1 student), "enough "Amounting to 38.71% (36 students)" good "amounting to 47.31% (44 students), and" very good "at 12.90% (12 students). Keywords: learning volleyball, motivation